2008
DOI: 10.1126/science.1154179
|View full text |Cite
|
Sign up to set email alerts
|

Surface Trapping of Atoms and Molecules with Dipole Rings

Abstract: The trapping of single molecules on surfaces without the formation of strong covalent bonds is a prerequisite for molecular recognition and the exploitation of molecular function. On nanopatterned surfaces, molecules may be selectively trapped and addressed. In a boron nitride nanomesh formed on Rh(111), the pattern consisted of holes 2 nanometers in diameter on a hexagonal superlattice, separated by about 3 nanometers. The trapping was further investigated with density functional theory and the photoemission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
247
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(271 citation statements)
references
References 22 publications
16
247
0
1
Order By: Relevance
“…The adsorbate is characterized by ''pores'' of about 2 nm diameter that strongly interact with the metal and elevated regions, where the interaction with the metal is weak, that form the connected ''wire'' network. The strong variation in bonding leads to a corresponding variation of the electrostatic potential above the monolayer that is responsible for trapping molecules [17]. The h-BN/ Rh(111) nanomesh is a very stable structure that withstands temperatures of 1,000 K and can be exposed to liquids without losing its properties.…”
Section: Introductionmentioning
confidence: 99%
“…The adsorbate is characterized by ''pores'' of about 2 nm diameter that strongly interact with the metal and elevated regions, where the interaction with the metal is weak, that form the connected ''wire'' network. The strong variation in bonding leads to a corresponding variation of the electrostatic potential above the monolayer that is responsible for trapping molecules [17]. The h-BN/ Rh(111) nanomesh is a very stable structure that withstands temperatures of 1,000 K and can be exposed to liquids without losing its properties.…”
Section: Introductionmentioning
confidence: 99%
“…This originates from the different reference substrates that are used in the two analyses, hBN/Sub and hBN/Sub. 1 Most interestingly, the above analysis shows that the hBN plane is within a capacitorlike linear potential profile along the z direction [ Fig. 4(a)].…”
Section: Resultsmentioning
confidence: 99%
“…First results on chemical functionalization of hBN have also been reported by trapping atoms or molecules on the dipole rings of epitaxial boron nitride [1]. The ionicity of the B-N bond induces a wide band gap in hBN with a direct optical transition for bulk hBN of about 5.9 eV [3,6,7].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…[11,12] For example, it has been shown that molecules can become trapped within nanopores of hexagonal boron nitride grown on Ru (0001) because of dipolar interactions; [13,14] similar results have also been observed for nanopores on the surface of bulk SiC. [15] Physisorption of a molecule to a surface (i.e., van der Waals bonding) is often not strong enough to fix the molecule's position at room temperature, particularly on the surface of bulk metal crystals.…”
mentioning
confidence: 99%